The quality of information provided by the most popular dementia videos on TikTok - Lukić, Stevo; Petrović, Jovana (Frontiers in Public Health, 2023)
of background data: Dementia is among the leading causes of death and disability worldwide, having a large impact not only on the affected person but also on the whole society.The internet is a popular and growing source of health-related information for patients, family members, carriers, and physicians. TikTok, one of the most popular social media platforms, is an important source for knowledge access and adoption. However, the quality of health information on TikTok has not been sufficiently studied.To evaluate quality of the information of most popular video of dementia shared on TikTok.Cross-sectional study.The top 100 popular videos on TikTok in response to the hashtag "dementia" were included in the study and grouped based on their source and content. The popularity of the videos was estimated using the numbers of likes, comments, and shares. The quality of health-related information was evaluated using the DISCERN score and the Global Quality Score (GQS).Results: Videos had a median duration of 33.29 seconds and a median number of 635100 likes, with a total number of 93698200 likes, 903859 comments, and 5310912 shares. The source (uploader) in 65% of the videos was family members, while only 4% were doctors. The content in 62% of the videos was lifestyle. Twelve percent of the videos were for fun. Videos had a median DISCERN score of 22.5 (IQR 20-27) and a median GQS of 2 (IQR 1-3). The videos uploaded by doctors had the highest quality scores and the lowest popularity.Most popular dementia videos on TikTok are mostly supplied by family members and are of poor quality. Regarding major public health issues of dementia, experts must provide appropriate and active assistance to patients in interpreting the information identified.